Efektivitas Sistem Constructed Wetland Dalam Menurunkan Jumlah Bakteri Patogen Pada Limbah Rumah Sakit - Joshua Christian Arransa Ranti; Haryati Bawole Sutanto; Guruh Prihatmo (Universitas Katolik Musi Charitas, 2020)
The wastewater produced in the hospital originates from activities carried out in the hospital, such as domestic waste, clinical waste, and laboratory waste. It contains many coliform bacteria. The bacteria were dangerous if it pollutes the environment because it can be the human’s disease. In general, hospitals have implemented wastewater treatment systems using disinfectants as tertiary treatment. Disinfectant itself can endanger the environment if used continuously. In addition, the use of disinfectants costs a lot. Therefore, this study uses a constructed wetland system as an alternative of the tertiary treatment using Echinodorus palaefolius. The results obtained from studies using this system are the percentage effectiveness of decreasing total coliform, BOD, nitrate, and phosphate. The removal efficiency of the total coliform, BOD, nitrate, & phosphate was 96,17%, 62,92%, 69,98%, & 63,53% respectively.